Individual differences in guilt proneness affect how people respond to moral tradeoffs between harm avoidance and obedience to authority. (February 2015) - Ent, Michael R.; Baumeister, Roy F.
Highlights: We studied guilt proneness and moral tradeoffs. Guilt proneness was positively related to valuing harm avoidance (versus obedience). The research highlights the role of guilt proneness in moral decision making. Abstract: High guilt proneness was associated with valuing harm avoidance more than obedience to authority on questionnaires (Study 1). Results from a laboratory study suggest that people high in guilt proneness, but not those low in guilt proneness, disobeyed an experimenter to prevent a confederate from suffering through an unpleasant task (Study 2). The present research highlights the role of guilt proneness in moral decision making.